2014
DOI: 10.1097/mrr.0000000000000083
|View full text |Cite
|
Sign up to set email alerts
|

Outcome measures capturing ICF domains in patient with total knee arthroplasty

Abstract: The International Classification of Functioning Disability and Health (ICF) represents a general framework for concepts of health and disability. The number of patients undergoing Total knee arthroplasty (TKA) is increasing worldwide. Capturing the different health-related ICF domains in this increasing number of patients with TKA requires clinicians and researchers to be familiar with the tools that can be used in daily clinical practice to capture these health-related domains. This paper aimed to review the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Systematic reviews and metaanalyzes examining the effectiveness of exercise therapy showed that preoperative physiotherapy patients (22). Although we planned this study with the knowledge that optimizing the preoperative quadriceps muscle strength plays a dominant role in achieving enhanced functional outcomes (12), we did not find a statistically significant increase in quadriceps muscle strength with NMES application. Further, results in the systematic review regarding the effect of NMES on quadriceps muscle strength in knee osteoarthritis alone or in combination with other therapeutic interventions are inconsistent (20), and a Cochrane review did not reach any conclusions about the application of NMES to strengthen quadriceps before or after TKA (23).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Systematic reviews and metaanalyzes examining the effectiveness of exercise therapy showed that preoperative physiotherapy patients (22). Although we planned this study with the knowledge that optimizing the preoperative quadriceps muscle strength plays a dominant role in achieving enhanced functional outcomes (12), we did not find a statistically significant increase in quadriceps muscle strength with NMES application. Further, results in the systematic review regarding the effect of NMES on quadriceps muscle strength in knee osteoarthritis alone or in combination with other therapeutic interventions are inconsistent (20), and a Cochrane review did not reach any conclusions about the application of NMES to strengthen quadriceps before or after TKA (23).…”
Section: Discussionmentioning
confidence: 81%
“…Evaluations were performed by a blinded investigator at baseline, preoperatively (after NMES application or 6-week surgical waiting period), weeks 4 and 12 postoperatively. Due to the increase in TKA surgery rates, a core set that complies with the International Functioning, Disability and Health Classification framework (12) and includes performance-based tests (recommended by OARSI) has been proposed (13). These studies were considered when determining the outcome measures.…”
Section: Methodsmentioning
confidence: 99%
“…The late‐life disability instrument (LLDI) (32) is a recommended tool for measuring level of participation restriction in this patient population (22). The LLDI has two dimensions: the frequency of performing socially defined life tasks and the limitation in capability of performing various social, community, and personal tasks.…”
Section: Methodsmentioning
confidence: 99%
“…Isometric quadriceps strength will be measured against a strap and HHD with the patient sitting and the knee at 90° flexion [ 59 ]. Isometric quadriceps strength has been tested at knee flexion angles of 45-90° [ 60 ] and is recommended to be tested at 60-90° knee flexion [ 61 ]. Isometric quadriceps strength measured with HHD at 90° knee flexion has demonstrated excellent reliability (ICC (2,1) = 0.96) and MDC 95 of 0.58 N/kg following TKA [ 59 ].…”
Section: Methodsmentioning
confidence: 99%